Unpardonable Sins: The Mentally Ill and Evangelicalism in America - Weaver, John (Journal of religion and popular culture, 2011)
This article explores the troubled relationship between evangelicals and the mentally ill community, focusing primarily on a Reformed/fundamentalist movement known as nouthetics or biblical counselling. I argue that for a large number of evangelicals, mentally ill people represent a diseased "other" population, in many ways as inherently "sinful" as gays and lesbians. Through this analysis, I promote a better understanding of mentally ill evangelicals, and more importantly, a better understanding of what the term "mentally ill" specifically denotes among evangelicals.